Prospecting biomarkers for diagnostic and therapeutic approaches in pythiosis - Chechi, Jéssica Luana [UNESP]; Rotchanapreeda, Tiwa; da Paz, Giselle Souza [UNESP]; Prado, Ana Carolina [UNESP]; Oliveira, Alana Lucena [UNESP]; Vieira, José Cavalcante Souza [UNESP]; Buzalaf, Marília Afonso Rabelo; Rodrigues, Anderson Messias; Dos Santos, Lucilene Delazari [UNESP]; Krajaejun, Theerapong; Bosco, Sandra de Moraes Gimenes [UNESP] (MDPI, 2021)
Pythiosis, whose etiological agent is the oomycete Pythium insidiosum, is a life-threatening disease that occurs mainly in tropical and subtropical countries, affecting several animal species. It is frequently found in horses in Brazil and humans in Thailand. The disease is difficult to diagnose because the pathogen’s hyphae are often misdiagnosed as mucoromycete fungi in histological sections. Additionally, there is no specific antigen to use for rapid diagnosis, the availability of which could improve the prognosis in different animal species. In this scenario, we investigated which P. insidiosum antigens are recognized by circulating antibodies in horses and humans with pythiosis from Brazil and Thailand, respectively, using 2D immunoblotting followed by mass spectrometry for the identification of antigens. We identified 23 protein spots, 14 recognized by pooled serum from horses and humans. Seven antigens were commonly recognized by both species, such as the heat-shock cognate 70 KDa protein, the heat-shock 70 KDa protein, glucan 1,3-beta-glucosidase, fructose-bisphosphate aldolase, serine/threonine-protein phosphatase, aconitate hydratase, and 14-3-3 protein epsilon. These results demonstrate that there are common antigens recognized by the immune responses of horses and humans, and these antigens may be studied as biomarkers for improving diagnosis and treatment.
Keywords: Antigens; Diagnosis; Immunoproteomics; Pythiosis; Pythium insidiosum; Therapy